Motivational and Emotional Attitude to Studying in High School Students of Different Sex and Age - Vartanova I.I (Moscow State University of Psychology and Education, 2019)
The purpose of this work was to study sex and age characteristics of emotional reflection of objects-values of school life in high school students. Experimental identification of the structure of the emotional-motivational profile was carried out using a factor analysis of assessments of 10 objects of school life according to the system of 25 adjective pairs in accordance with the Semantic Dif ferential scale. The analysis was conducted separately for each of the four groups of schoolchildren (two schools in Moscow with the traditional training paradigm): the younger group (8-9 grades, 14-15 years old) boys (52) and girls (57), the older groups (10-11 classes, 16-17 years old) boys (96) and girls (100).This made it possible to identify and describe the structure and qualitative specificity of the emotional relationship of high school students of different sex and age. It is revealed that with age there is a tendency of differentiation and transformation of the content of certain motives: for boys in the sphere of self-affirmation and for girls in the sphere of affiliation and status motivation. Obligation motivation (learning as a necessity) turned out to be similar for groups of boys and girls and varies insignificantly with age.